Intravenous methylprednisolone in HTLV-I associated myelopathy/tropical spastic paraparesis (HAM/TSP) - Abelardo Q-C Araújo (Arquivos de Neuro-Psiquiatria, 1993)
HTLV-I (Human T-lymphotropic virus type I) associated myelopathy/tropical spastic paraparesis (HAM/TSP) is an immunomediated myelopathy induced by the HTLV-I. Some patients, specially those from Japan, seem to have a good response to steroid treatment. However, this has not been found in other regions of the world. High dose intravenous methylprednisolone has been used with success in patients with relapses of multiple sclerosis (MS), another autoimmune disease of the central nervous system. To test the effectiveness of methylprednisolone in patients with HAM/TSP, we devised an open trial in 23 patients. We found a very limited benefit of this form of treatment in these patients. Only one patient, who had the shortest disease duration (five months) in the whole group, showed a sustained benefit. We speculate that those patients with a shorter history, with presumably less demye-lination and more inflammatory lesions, would show a better response to immunossupressive treatments.